Combined Material Recycling Study with Aesthetic of Entropy and Place Making - Yifeng Wen (The Scientific World Journal)
Green building is a hot topic today. The place making and urban cultures are also important issues in postindustrial society. The industrial heritage renovation projects provide a research opportunity in combination with both aspects. This paper tries to shed new light on this issue by interdisciplinary methods, to study six Guangzhou industrial heritage renovation projects, giving aesthetic values for six sites concerning place making and culture creation, especially giving an explanation for old building material’s aesthetic performance in terms of concepts “entropy” and “archetype.” The conclutions regard: the six places are brand spaces of “authentic Guangzhou” that make local experiential knowledge, emotional significance and creative communities in combination with historical and cultural narratives.